Enhancing Food Court Experience Through Design Thinking - Deatri Arumsari Agung; Stefanus Amadeo Elbaharikusuma (Teknika, 2026)
Despite widespread digital transformation in the food and beverage service industry, food courts in shopping malls largely remain dependent on conventional, queue-based ordering systems. This results in persistent inefficiencies and a diminished customer experience. This study advances existing research by developing and empirically validating a user-centered digital ordering and cashless payment prototype for food court environments. Food courts remain an underexplored service context compared to standalone restaurants and self-service kiosks. Employing a Design Thinking methodology, this qualitative study integrates empathize stage interviews with usability testing to achieve methodological triangulation. This ensures both experiential depth and design validation. Five Generation Z users in Surabaya participated as actual end users. This addresses a key limitation of prior studies that relied primarily on business owners or designers rather than customers. User insights were synthesized into a Point of View (POV) statement that directly informed ideation and iterative prototyping. The resulting prototype prioritizes visual clarity, intuitive navigation, and accessibility. These features are achieved through image-supported menus, readable typography, adequate color contrast, and icon-based interaction. Testing results indicate that the prototype eliminates physical queuing, while users reported enhanced efficiency and greater satisfaction. The study contributes theoretically by extending the application of Design Thinking to shared-service food court systems. Practically, it offers empirically grounded UI/UX design principles for scalable digital ordering solutions in high-traffic service environments.